Pengembangan Desain Kurikulum Maritim di Jepara - Farchan, Achmad; Muhtadi, Ali (Curriculum and Educational Technology Department, 2019)
This research aims to develop maritime curriculum design in accordance with the needs of the maritime community on the coast of Jepara. The curriculum model used in this research was the D.K. Wheeler by employing several steps including selecting the goals, selecting the learning experiences, selecting the content, organizing the learning experiences and evaluating the process. The techniques of data collection in this research were observations and interviews. Data were analyzed using descriptive-qualitative. Based on the results of the study, curriculum design based on maritime consist of five indicators that need to be considered, the curriculum design should (1) aiming to develop marine potential; (2) based the content on the reality of people?s lives; (3) using a problem solving approach; (4) developing students? life skills and (5) encouraging community participation. The learning experinces that need of the maritime community are technology-based fishing techniques, processing of catches, catching preservation techniques, management of salt ponds, ship engine engineering and fishing gear innovations. Abstrak Penelitian ini bertujuan mengembangkan desain kurikulum bidang kemaritiman yang relevan dengan kebutuhan masyarakat maritim di pesisir pantai Jepara. Model pengembangan desain kurikulum yang digunakan adalah model D.K Wheeler. Langkah penelitian pengembangan ini meliputi seleksi tujuan, seleksi pengalaman belajar, seleksi konten, pengorganisasian pengalaman belajar, dan evaluasi. Teknik pengumpulan data berupa observasi dan wawancara. Analisis data yang digunakan adalah deskriptif kualitatif. Berdasarkan hasil penelitian, setidaknya desain kurikulum bidang kemaritiman memuat lima indikator yaitu; (1) bertujuan mengembangkan potensi kelautan; (2) konten kurikulum berdasarkan pada realitas kehidupan masyarakat; (3) menggunakan pendekatan pemecahan masalah; (4) mengembangkan keterampilan hidup peserta didik; dan (5) mendorong partisipasi masyarakat. Sedangkan pengalaman belajar yang relevan dengan kebutuhan masyarakat maritim diantaranya teknik melaut berbasis teknologi, pengolahan hasil tangkap, teknik pengawetan hasil tangkap, pengolahan tambak garam, teknik mesin kapal, dan inovasi alat tangkap. Keywords: curriculum deisgn; maritime community; coast of Jepara